Pengaruh Edukasi Metode Cbia Terhadap Pengetahuan Swamedikasi Berdasarkan Konsep Dagusibu Di Kelompok PKK Desa Sawangan Kecamatan Kuwarasan Kabupaten Kebumen - Ervina Laely Nuswantari; Tatang Tajudin; Tri Fitri Yana Utami (Pharmaqueous : Jurnal Ilmiah Kefarmasian, 2023)
Based on Badan Pusat Statistik (2022), more than 70% of sick people in Indonesia doing self-medicate (swamedikasi) when they have mild symptoms of illness without consulting a doctor. Self-medication is widely carried out by various group of people, one of which is housewives in PKK group Desa Sawangan, Kecamatan Kuwarasan, Kabupaten Kebumen. â€œMothersâ€ are determining part of health in the household, including in making drug selection decisions, so it needs to be accompanied by adequate knowledge about the proper implementation of selfmedication. CBIA (Cara Belajar Insan Aktif) program can be a solution to existing problems. CBIA is one of the community empowerement activities used in educating people to choose and use the right drugs in self-medication. This study aims to find out an overview of self-medicated knowledge and find out the influence of the application of the CBIA method to increase knowledge about drug self-medication based on the DAGUSIBU concept (Dapatkan, Gunakan, Simpan, Buang). This research method is a quantitative method of experimental type, one-grup pretest-posttest. Amount of sample in this research are 67 people was selected using the Purposive Sampling Method with inclusion dan exclusion criteria set by the researcher. The data analysis used was a paired t-test statistical test and obtained a signification value (2-tailed) of 0,001 <0,05 which showed a significant difference between the pretest dan post-test values. The CBIA program is effective in increasing knowledge of the PKK Community in Desa Sawangan, Kecamatan Kuwarasan, Kabupaten Kebumen.